The Role of Islamic Financial Institutions in Establishing Social Responsibility: An Analytical Study - Hamza, Tiouane; Medoukh, Madjida (Finance and Business Economies Review, 2022)
The study aims to know the social role entrusted to Islamic financial institutions, which is derived in its origin from the legal texts that urged cooperation and synergy between the groups of society with limited and no income, by trying to reach the embodiment of the legitimate purposes through zakat, good loan and others, whose results are directly reflected on Social development. We have relied on the descriptive analytical approach by collecting data issued in official reports of reliable scientific journals. The study came to the conclusion that Islamic financial institutions contribute very little to social responsibility globally, and the reason for this is the failure of Islamic financial institutions to disclose the size of zakat, charitable works, charity and others in their financial reports, as well as the small size of the sample approved in financial reports (360). Institution only), also the existence of customer risks associated with good loans granted by Islamic banks to their customers, which are moral risks that result in non-payment or default in the repayment of the granted loans